Checkpoint inhibitors in metastatic papillary renal cell carcinoma. (September 2021) - de Vries-Brilland, M.; McDermott, D.F.; Suárez, C.; Powles, T.; Gross-Goupil, M.; Ravaud, A.; Flippot, R.; Escudier, B.; Albigès, L.
Highlights: Papillary renal cell carcinoma (pRCC) is the most common non-clear cell renal cell carcinoma. The treatment landscape of metastatic pRCC relied so far on targeted therapies. Development of immune checkpoint inhibitors (ICI) is now underway in patients with pRCC, with efficacy of ICI as single agent remains limited. Combinations with tyrosine-kinase inhibitors, notably with anti-MET inhibitors, harbor promising response rates. Abstract: Papillary Renal Cell Carcinoma (pRCC) is the most common non-clear cell RCC (nccRCC) and a distinct entity, although heterogenous, associated with poor outcomes. The treatment landscape of metastatic pRCC (mpRCC) relied so far on targeted therapies, mimicking previous developments in metastatic clear-cell renal cell carcinoma. However, antiangiogenics as well as mTOR inhibitors retain only limited activity in mpRCC. As development of immune checkpoint inhibitors (ICI) is now underway in patients with mpRCC, we aimed at discussing early activity data and potential for future therapeutic strategies in monotherapy or combination. Expression of immune checkpoints such as PD-L1 and infiltrative immune cells in pRCC could provide insights into their potential immunogenicity, although this is currently poorly described. Based on retrospective and prospective data, efficacy of ICI as single agent remains limited. Combinations with tyrosine-kinase inhibitors, notably with anti-MET inhibitors, harbor promising response rates and may enter the standard of care in untreated patients. Collaborative work is needed to refine the molecular and immune landscape of pRCC, and pursue efforts to set up predictive biomarker-driven clinical trials in these rare tumors.